Health related quality of life among patients with chronic hepatitis C: a cross-sectional study of sociodemographic, psychopathological and psychiatric determinants - Bruno Cópio Fábregas; Renata Eliane de Ávila; Marjore Novaes Faria; Alexandre Sampaio Moura; Ricardo Andrade Carmo; Antonio Lúcio Teixeira (Brazilian Journal of Infectious Diseases)
INTRODUCTION: Chronic hepatitis C virus infection patients have higher rates of psychiatric disorders than the general population. Chronic hepatitis C virus infection is known to be associated with impaired health related quality of life. To our knowledge, there is no previous research of health related quality of life in chronic hepatitis C patients that combined structured psychiatric interview and careful psychopathological evaluation, including depression, anxiety and fatigue instruments. The aim of this study was to evaluate health related quality of life of chronic hepatitis C patients and to investigate the association with sociodemographic, psychopathological and psychiatric factors. MATERIALS AND METHODS: Eighty-one individuals with chronic hepatitis C virus infection receiving care at a Brazilian public university-based outpatient service for infectious diseases were enrolled in the study. The World Health Organization Quality of Life Scale Brief Version was used to assess health related quality of life. Standard psychiatric interview (Mini International Neuropsychiatric Interview-Plus) was conducted to establish Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Axis I psychiatric diagnosis. Further instruments completed psychopathological investigation: Beck Depression Inventory, Hospital Anxiety and Depression Scale, Brief Fatigue Inventory, Hamilton Depression Scale and Hamilton Anxiety Scale. Pearson Chi-Square and Kruskal-Wallis were performed for categorical and continuous univariate analysis, respectively. Correlation between psychopathological and health related quality of life scores was performed according to Spearman's correlation. Multivariate analysis was performed according to stepwise forward ordinal logistic regression. The significance threshold was fixed at α = 0.05. RESULTS: Depressive disorders were associated with worse scores in overall health related quality of life and in all domains. Fatigue was associated with lower scores in physical and psychological domains, and married status with higher scores in psychological health related quality of life. We found strong correlation among scores of depression, fatigue and health related quality of life. CONCLUSION: Depression and fatigue must be properly investigated and managed in HCV patients in order to improve HRQL. WHOQOL-BREF proved to be a useful instrument to assess HRQL in HCV patients.